Conductive paste and preparation method and application thereof
By using a single carbon nanotuba and graphene conductive, formation of high -electrical and high flexibility conductive networks are formed to solve the problem of conductive performance of the volume change caused by the volume changes during the battery cycle of the silicon -based material. Battery cycle performance and life improvement.
Patent Information
- Application Number
- CN202411790966.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-01-24
AI Technical Summary
The volume of the silicon-based negative electrode material changes greatly during the battery charge and discharge cycle, making it difficult for the conductive agent to maintain a good conductive network, affecting the cycling performance and life of the battery.
Using a conductive slurry composed of single-walled carbon nanotubes and graphene, by controlling the graphitization degree of single-walled carbon nanotubes and the number of graphene layers, a conductive network with high conductivity, high flexibility and high dispersion is formed. The negative electrode material is coated to inhibit volume expansion.
It improves the circulation performance and life of the battery, ensure the conductivity performance, effectively suppress the expansion of the negative electrode material, and extend the service life of the battery.
Smart Images

Figure CN119361213A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of conductive materials, and in particular to a conductive paste and a preparation method and application thereof. Background Art
[0002] Conductive slurry is widely used in the field of secondary batteries. For example, conductive slurry can be used to prepare negative electrode slurry. The conductive material in the conductive slurry can be used as a conductive agent for the negative electrode material. The conductive properties of the conductive agent in the negative electrode material play an important role in the battery's rate performance, cycle performance and capacity.
[0003] At present, the capacity requirements for secondary batteries are getting higher and higher. Researchers' research on high-energy-density negative electrode active materials has found that the gram capacity of silicon-based negative electrode materials is much higher than that of carbon materials. However, silicon-based materials have a serious volume effect. During battery charging, the volume of silicon-based negative electrode materials will expand, and during battery discharge, the volume of silicon-based negative electrode materials will shrink. Due to the large volume change of the negative electrode material during the charge and discharge cycle, it is difficult for the conductive agent in the negative electrode material to maintain a good conductive network, which in turn affects the conductive properties and the cycle performance of the battery. In addition, when the secondary battery is repeatedly charged and discharged, the silicon-based negative electrode material is easy to break and differentiate, which will further reduce the cycle life of the secondary battery. Summary of the invention
[0004] In view of this, the embodiments of the present application provide a conductive paste and a preparation method and application thereof to solve at least one problem existing in the background technology.
[0005] In a first aspect, an embodiment of the present application provides a conductive paste comprising single-walled carbon nanotubes and graphene;
[0006] The mass ratio of the single-walled carbon nanotube to the graphene is 1:9 to 1:1;
[0007] In X-ray diffraction analysis, the half-width of the diffraction peak of the single-walled carbon nanotube in the 2θ range of 20° to 30° is 5° to 12°.
[0008] In combination with the first aspect of the present application, in an optional embodiment, the conductive paste also includes a dispersant and a solvent. Based on the total weight of the conductive paste as 100%, the weight percentage of the single-walled carbon nanotubes is 0.05% to 0.5%, the weight percentage of the graphene is 0.25% to 2.5%, the weight percentage of the dispersant is 0.2% to 1%, and the weight percentage of the solvent is 96% to 99.5%.
[0009] In conjunction with the first aspect of the present application, in an optional embodiment, the single-walled carbon nanotube satisfies at least one of the following characteristics:
[0010] (1) The IG / ID of the Raman spectrum of the single-walled carbon nanotube is 40 to 120; preferably, the IG / ID of the Raman spectrum of the single-walled carbon nanotube is 50 to 90;
[0011] (2) The specific surface area of the single-walled carbon nanotube is 500 m 2 / g~1200m 2 / g;
[0012] (3) The purity of the single-walled carbon nanotubes is greater than or equal to 99%;
[0013] (4) The length of the single-walled carbon nanotube is 1 μm to 30 μm;
[0014] (5) The diameter of the bundle of single-walled carbon nanotubes is 10 nm to 50 nm.
[0015] In conjunction with the first aspect of the present application, in an optional implementation, the graphene satisfies at least one of the following characteristics:
[0016] (1) IG / ID of the Raman spectrum of the graphene is 1 to 10;
[0017] (2) The specific surface area of the graphene is 20 m 2 / g~100m 2 / g;
[0018] (3) The purity of the graphene is greater than or equal to 99%;
[0019] (4) The number of graphene layers is less than or equal to 10.
[0020] In conjunction with the first aspect of the present application, in an optional embodiment, the conductive paste satisfies at least one of the following characteristics:
[0021] (1) The particle sizes D90 and D50 of the conductive paste satisfy: D90 / D50 is 2 to 8;
[0022] (2) the IG / ID of the Raman spectrum of the conductive paste is 10 to 60;
[0023] (3) The thixotropic index of the conductive paste is 5 to 15;
[0024] (4) The viscosity of the conductive paste is 2000 mPa·s to 8000 mPa·s.
[0025] In a second aspect, an embodiment of the present application provides a method for preparing a conductive paste, the method comprising:
[0026] The single-walled carbon nanotubes, the first dispersant and the first solvent are mixed and dispersed uniformly to obtain a first mixture; in an X-ray diffraction analysis, the half-height width of the diffraction peak of the single-walled carbon nanotubes in the 2θ range of 20° to 30° is 5° to 12°;
[0027] The graphene, the second dispersant and the second solvent are mixed and dispersed uniformly to obtain a second mixture; the mass ratio of the single-walled carbon nanotube to the graphene is 1:9 to 1:1;
[0028] The first mixture and the second mixture are mixed and dispersed uniformly to obtain the conductive paste.
[0029] In conjunction with the second aspect of the present application, in an optional embodiment, the step of preparing the first mixture satisfies at least one of the following characteristics:
[0030] (1) The IG / ID of the Raman spectrum of the single-walled carbon nanotube is 40 to 120;
[0031] (2) The specific surface area of the single-walled carbon nanotube is 500 m 2 / g~1200m 2 / g;
[0032] (3) The purity of the single-walled carbon nanotubes is greater than or equal to 99%;
[0033] (4) The particle size D50 of the first mixture is 5 μm to 50 μm.
[0034] In conjunction with the second aspect of the present application, in an optional embodiment, the step of preparing the second mixture satisfies at least one of the following characteristics:
[0035] (1) IG / ID of the Raman spectrum of the graphene is 1 to 10;
[0036] (2) The specific surface area of the graphene is 20 m 2 / g~100m 2 / g;
[0037] (3) The purity of the graphene is greater than or equal to 99%;
[0038] (4) The particle size D50 of the second mixture is less than or equal to 6 μm.
[0039] In conjunction with the second aspect of the present application, in an optional embodiment, the conductive paste satisfies at least one of the following characteristics:
[0040] (1) The particle sizes D90 and D50 of the conductive paste satisfy: D90 / D50 is 2 to 8;
[0041] (2) the IG / ID of the Raman spectrum of the conductive paste is 10 to 60;
[0042] (3) The thixotropic index of the conductive paste is 5 to 15;
[0043] (4) The viscosity of the conductive paste is 2000 mPa·s to 8000 mPa·s;
[0044] (5) The length of the single-walled carbon nanotubes in the conductive paste is 1 μm to 30 μm;
[0045] (6) The diameter of the bundle of single-walled carbon nanotubes in the conductive paste is 10 nm to 50 nm;
[0046] (7) The number of graphene layers in the conductive paste is less than or equal to 10;
[0047] (8) Taking the total weight of the conductive paste as 100%, in the conductive paste, the weight percentage of the single-walled carbon nanotubes is 0.05% to 0.5%, the weight percentage of the graphene is 0.25% to 2.5%, the sum of the weight percentages of the first dispersant and the second dispersant is 0.2% to 1%, and the sum of the weight percentages of the first solvent and the second solvent is 96% to 99.5%.
[0048] In a third aspect, embodiments of the present application provide use of a conductive paste prepared by the conductive paste described in any one of the first aspect or the conductive paste prepared by the method for preparing the conductive paste described in any one of the second aspect in a lithium-ion battery.
[0049] The conductive paste and its preparation method and application provided in the embodiments of the present application, the conductive paste includes single-walled carbon nanotubes and graphene; the mass ratio of the single-walled carbon nanotubes to the graphene is 1:9 to 1:1; in the X-ray diffraction analysis, the half-width of the diffraction peak of the single-walled carbon nanotubes in the 2θ range of 20° to 30° is 5° to 12°. The conductive paste in the embodiment of the present application includes single-walled carbon nanotubes and graphene. The half-width of the diffraction peak of the single-walled carbon nanotubes in the 2θ range of 20° to 30° is controlled to 5° to 12°, so that the single-walled carbon nanotubes have a suitable degree of graphitization, thereby having high conductivity, high flexibility and high dispersibility. By controlling the mass ratio of single-walled carbon nanotubes and graphene to 1:9 to 1:1, the conductive paste can have better conductive properties and suitable viscosity. When the conductive material is applied to the negative electrode material, the single-walled carbon nanotubes with high conductivity, high flexibility and high aspect ratio can be better connected with the graphene with a two-dimensional planar structure and high conductivity to form a dense and complete conductive network, which tightly coats the negative electrode material, thereby suppressing the expansion of the negative electrode material, and thus effectively improving the cycle performance of the battery while ensuring the conductive performance.
[0050] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0052] Figure 1 A schematic diagram of a process for preparing a conductive paste provided in an embodiment of the present application;
[0053] Figure 2 is a scanning electron microscope image of the conductive paste in Example 1;
[0054] Figure 3 is a scanning electron microscope image of the conductive paste in Example 2;
[0055] Figure 4 is a scanning electron microscope image of the conductive paste in Example 3;
[0056] Figure 5 is a transmission electron microscope image of the conductive paste in Example 1;
[0057] Figure 6 is a scanning electron microscope image of the conductive paste in Comparative Example 1;
[0058] Figure 7 is a scanning electron microscope image of the conductive paste in Comparative Example 2;
[0059] Figure 8 is a scanning electron microscope image of the negative electrode material containing the conductive paste in Example 1;
[0060] Fig. 9 is a scanning electron microscope image of the negative electrode material containing the conductive paste in Comparative Example 1;
[0061] Fig.10 This is a scanning electron microscope image of the negative electrode material containing the conductive paste in Comparative Example 2. DETAILED DESCRIPTION
[0062] In order to make the technical scheme and beneficial effects of the present invention more obvious and easy to understand, the following is described in detail by combining the accompanying drawings and listing specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually based on conventional experimental conditions. The reagents and raw materials used in the present invention are commercially available unless otherwise specified.
[0063] In the following description, a large number of specific details are given to provide a more thorough understanding of the present application. However, it is obvious to those skilled in the art that the present application can be implemented without one or more of these details. In other examples, in order to avoid confusion with the present application, some technical features known in the art are not described; that is, all features of the actual embodiments are not described here, and well-known functions and steps are not described in detail.
[0064] The purpose of the terms used herein is only to describe specific embodiments and is not intended to be limiting of the present application. When used herein, the singular forms "a", "an" and "said / the" are also intended to include plural forms, unless the context clearly indicates otherwise. The terms "consisting of" and / or "comprising", when used in this specification, determine the presence of the features, integers, steps, operations, elements and / or parts, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, parts and / or groups. When used herein, the term "and / or" includes any and all combinations of the relevant listed items.
[0065] In order to thoroughly understand the present application, detailed steps and detailed structures will be presented in the following description to illustrate the technical solution of the present application. The preferred embodiments of the present application are described in detail below, but in addition to these detailed descriptions, the present application may also have other implementation methods.
[0066] Unless otherwise defined, technical and scientific terms used in this application have the same meanings as those in the technical field to which this application belongs.
[0067] If no specific techniques or conditions are specified in the following examples, the conventional techniques or conditions described in the literature in the art, or the conditions recommended by the product instructions and the manufacturer are generally used. The numerical ranges in the following examples all include the endpoint values.
[0068] Single-walled carbon nanotubes have high specific surface area, high aspect ratio and good crystal structure, and have good conductivity. Therefore, single-walled carbon nanotubes are suitable for use in negative electrode slurries as conductive agents in negative electrode materials. However, as the battery continues to charge and discharge cycles, the negative electrode material is prone to large volume changes, which can easily lead to surface damage or even breakage of the single-walled carbon nanotubes, making it difficult for the single-walled carbon nanotubes to maintain a good conductive network in the negative electrode material, thereby reducing the cycle life of the battery. As a two-dimensional planar conductive material, graphene usually has a comparable aspect ratio and a relatively large sheet diameter. When the thickness of graphene is too thick, it is not conducive to the transmission of active ions. Therefore, graphene used in negative electrode slurries is usually reduced in size, but smaller graphene sheets cannot be well bridged in silicon-based negative electrode materials, and it is difficult to form an effective conductive network, so it is of little help in improving conductivity.
[0069] Based on this, an embodiment of the present application provides a conductive paste, which includes single-walled carbon nanotubes and graphene; the mass ratio of the single-walled carbon nanotubes to the graphene is 1:9 to 1:1; in X-ray diffraction analysis, the half-width of the diffraction peak of the single-walled carbon nanotubes in the 2θ range of 20° to 30° is 5° to 12°.
[0070] In X-ray diffraction analysis, the half-width of the diffraction peak of single-walled carbon nanotubes within the diffraction angle range (also called XRD half-width) can be used to characterize the degree of graphitization of single-walled carbon nanotubes. When the XRD half-width of the single-walled carbon nanotubes is small, it indicates that the degree of graphitization of the single-walled carbon nanotubes is high, and the single-walled carbon nanotubes have high conductivity and flexibility, but the dispersibility of the single-walled carbon nanotubes is poor, and it is not easy to disperse evenly in the conductive paste, so it is not conducive to forming a uniform and dense conductive network; when the XRD half-width of the single-walled carbon nanotubes is large, the degree of graphitization of the single-walled carbon nanotubes is low, and the conductivity and flexibility of the single-walled carbon nanotubes are poor, so it will affect the conductivity of the conductive paste. In the embodiment of the present application, the half-width of the diffraction peak of the single-walled carbon nanotube in the 2θ range of 20° to 30° is controlled to be 5° to 12°, for example, it can be 5°, 6°, 7°, 8°, 9°, 10°, 11°, 12° or any value between any two of the above numerical ranges, so that the single-walled carbon nanotube has a suitable degree of graphitization, thereby having high conductivity, high flexibility and high dispersibility. When the masses of single-walled carbon nanotubes and graphene are relatively small, the content of graphene in the conductive paste is relatively high and the content of single-walled carbon nanotubes is relatively low, and it is difficult for single-walled carbon nanotubes to play an effective bridging role, that is, single-walled carbon nanotubes cannot effectively connect with graphene to form a dense conductive network; when the masses of single-walled carbon nanotubes and graphene are relatively large, the content of single-walled carbon nanotubes in the conductive paste is relatively high and the content of graphene is relatively low. When the conductive paste is applied to the negative electrode material, it is difficult for graphene to play an effective coating role, that is, single-walled carbon nanotubes and graphene cannot form a conductive network that effectively coats the negative electrode material to inhibit the volume expansion of the negative electrode material. In the embodiment of the present application, by controlling the mass ratio of single-walled carbon nanotubes and graphene to 1:9 to 1:1, for example, it can be 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9 or any value between any two of the above numerical ranges, the conductive slurry can have better conductivity and suitable viscosity, and when the conductive material is applied to the negative electrode material, the single-walled carbon nanotubes with high conductivity, high flexibility and high aspect ratio and the graphene with two-dimensional planar structure and high conductivity can be better connected to form a dense and complete conductive network, tightly coating the negative electrode material, thereby inhibiting the expansion of the negative electrode material, and thus effectively improving the cycle performance of the battery while ensuring the conductive performance.
[0071] In some embodiments, the conductive paste further includes a dispersant and a solvent. Based on the total weight of the conductive paste as 100%, the weight percentage of the single-walled carbon nanotubes can be 0.05% to 0.5%, for example, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5% or any value between any two of the above numerical ranges, and the weight percentage of graphene can be 0.25% to 2.5%, for example, The weight percentage of the dispersant is 0.25%, 0.5%, 1%, 1.5%, 2%, 2.5% or any value between any two of the above numerical ranges, the weight percentage of the dispersant is 0.2% to 1%, for example, it can be 0.2%, 0.4%, 0.6%, 0.8%, 1% or any value between any two of the above numerical ranges, and the weight percentage of the solvent is 96% to 99.5%, for example, it can be 96%, 97%, 98%, 99%, 99.5% or any value between any two of the above numerical ranges. By controlling the weight percentage of the single-walled carbon nanotubes, graphene, the dispersant and the solvent within the above range, the single-walled carbon nanotubes and graphene can be more evenly dispersed in the solvent to form a conductive paste with good conductivity, suitable viscosity and high stability, thereby facilitating the application of the conductive paste.
[0072] Exemplarily, the dispersant may include one or more of polyvinyl pyrrolidone, polyvinyl alcohol, silane coupling agent, polyacrylic acid, carboxymethyl cellulose salt, ethyl cellulose, hydroxypropyl cellulose, chitosan, etc. The solvent may include one or more of water, ethanol, isopropanol, etc. In a specific embodiment, the dispersant is sodium carboxymethyl cellulose, and the solvent is deionized water. Further, the number average molecular weight of sodium carboxymethyl cellulose may be 20000 g / mol to 100000 g / mol, and the weight average molecular weight may be 40000 g / mol to 100000 g / mol. In this way, the single-walled carbon nanotubes and graphene can be better dispersed to form a more uniform and dense conductive network, thereby improving the conductive properties of the conductive paste.
[0073] In the study of carbon materials such as graphene and carbon nanotubes, Raman spectroscopy can be used to characterize the structural information of carbon materials. Both G peak and D peak are Raman characteristic peaks of carbon atom crystals. Among them, G peak reflects the degree of graphitization of carbon materials, and D peak reflects the defects of carbon materials. IG and ID represent the intensity of G peak and D peak respectively. The larger the IG value, the higher the degree of graphitization of carbon materials, and the larger the ID value, the more defects of carbon materials. The IG / ID value is usually used to characterize the performance of carbon materials.
[0074] When the IG / ID of the Raman spectrum of the single-walled carbon nanotube is small, it indicates that the single-walled carbon nanotube has more surface defects, and the conductivity and flexibility of the single-walled carbon nanotube are poor, which will affect the performance of the conductive paste; when the IG / ID of the Raman spectrum of the single-walled carbon nanotube is large, it indicates that the single-walled carbon nanotube has fewer surface defects, the intermolecular force is strong, the conductivity and flexibility of the single-walled carbon nanotube are good, but the dispersibility of the single-walled carbon nanotube is poor, which will also affect the performance of the conductive paste. Therefore, in some specific embodiments, the IG / ID of the Raman spectrum of the single-walled carbon nanotube can be 40 to 120. In this way, the surface defect degree of the single-walled carbon nanotube can be moderate, taking into account good conductivity, flexibility and dispersibility. Due to the good dispersibility of the single-walled carbon nanotube, it can be better dispersed in the solvent to form a uniform and dense conductive network, so that the conductive performance of the conductive paste is better. Due to the good flexibility of single-walled carbon nanotubes, when the conductive slurry is applied to the negative electrode material, the conductive network formed by the single-walled carbon nanotubes and graphene has a stronger wrapping effect, which can better inhibit the volume expansion of the negative electrode material and thus better improve the battery's cycle performance.
[0075] In some specific embodiments, the specific surface area of the single-walled carbon nanotubes can be 500 m 2 / g~1200m 2 In this way, the dispersion of single-walled carbon nanotubes is more favorable, the viscosity of the conductive paste can be made appropriate, and the conductive performance is better.
[0076] In some specific embodiments, the purity of the single-walled carbon nanotubes can be greater than or equal to 99%. In this way, there are almost no impurities in the single-walled carbon nanotubes, and they have better conductivity, thereby further improving the conductivity of the conductive paste. Furthermore, the purity of the single-walled carbon nanotubes can be greater than 99%.
[0077] When the length of the single-walled carbon nanotubes in the conductive slurry is short, it is not conducive to the interconnection between the single-walled carbon nanotubes and graphene to form a dense and stable conductive network; when the length of the single-walled carbon nanotubes in the conductive slurry is long, it will affect the dispersion of the single-walled carbon nanotubes, resulting in a higher viscosity of the conductive slurry, which will affect the stability and application of the conductive slurry. Therefore, in some specific embodiments, the length of the single-walled carbon nanotubes in the conductive slurry can be 1μm to 30μm. In this way, the viscosity of the conductive slurry can be appropriate and the conductive performance can be good. When the conductive slurry is applied to the negative electrode material, the single-walled carbon nanotubes and graphene are interconnected to form a dense and stable conductive network, which can better cover the negative electrode material, thereby better suppressing the volume expansion of the negative electrode material, and further improving the cycle performance of the battery.
[0078] In some embodiments, the bundle diameter of the single-walled carbon nanotubes in the conductive slurry can be 10 nm to 50 nm. Controlling the bundle diameter of the single-walled carbon nanotubes within the above range can form a better and more stable connection between the single-walled carbon nanotubes and graphene, facilitating the formation of a denser and more stable conductive network. In the actual application of the negative electrode material, the volume expansion of the negative electrode material can be better suppressed, thereby further improving the cycle performance of the battery.
[0079] It should be noted that the bundle of single-walled carbon nanotubes is not necessarily a relatively regular cylindrical shape, and the bundle diameter mentioned above can be understood as the maximum size of the bundle of single-walled carbon nanotubes in the radial direction of the bundle.
[0080] In some embodiments, the IG / ID of the Raman spectrum of graphene may be 1 to 10. In this way, the graphene can have both good conductivity and dispersibility, so that the conductive paste has good conductivity and suitable viscosity.
[0081] In some embodiments, the specific surface area of graphene can be 20 m 2 / g~100m 2 / g. In this way, it is more conducive to the dispersion of graphene, and the viscosity of the conductive paste can be appropriate, and the conductive performance is better.
[0082] In some embodiments, the purity of graphene can be greater than or equal to 99%. In this way, there are almost no impurities in the graphene, and it has better conductivity, thereby further improving the conductivity of the conductive paste. Furthermore, the purity of graphene can be greater than 99%.
[0083] When the number of graphene layers in the conductive paste is large, the diameter of the graphene sheets will be large, which is not conducive to the interconnection between the graphene and the single-walled carbon nanotubes. In some specific embodiments, the number of graphene layers in the conductive paste can be less than or equal to 10. In this way, the diameter of the graphene sheets in the conductive paste can be smaller, the dispersion is better, and it is more conducive to interconnection with the single-walled carbon nanotubes, and the coating effect of the conductive network formed by the single-walled carbon nanotubes and graphene is better. Further, the number of graphene layers can be less than 10.
[0084] When the particle size D90 / D50 of the conductive paste is large, it indicates that the particle size distribution range of the single-walled carbon nanotubes and graphene in the conductive paste is wide, and the size difference of the particles is large, which easily leads to uneven dispersion and high viscosity of the conductive paste, thereby affecting the conductive performance and stability of the conductive paste; when the particle size D90 / D50 of the conductive paste is small, it indicates that the particle size distribution of the single-walled carbon nanotubes and graphene in the conductive paste is too uniform, so that the aspect ratio of the single-walled carbon nanotubes will be reduced, thereby not utilizing the single-walled carbon nanotubes and graphene to form a dense conductive network. Therefore, in some specific embodiments, the particle sizes D90 and D50 of the conductive paste satisfy: D90 / D50 is 2 to 8. In this way, the conductive performance and stability of the conductive paste can be better.
[0085] It should be noted that D50 and D90 are usually used to indicate the average particle size of a material. When the cumulative particle size distribution percentage of a material reaches 50%, the corresponding particle size is D50, that is, particles with a particle size greater than D50 account for 50%, and particles with a particle size less than D50 also account for 50%. Therefore, D50 is also called the median particle size. When the cumulative particle size distribution percentage of a material reaches 90%, the corresponding particle size is D90.
[0086] In some embodiments, the IG / ID of the Raman spectrum of the conductive paste may be 10 to 60. This ensures that the conductive paste has good conductive properties.
[0087] In the embodiment of the present application, the Raman spectrum testing method of the conductive paste is to apply the conductive paste on polyethylene terephthalate (PET), dry it, and then perform Raman spectrum testing to obtain the IG / ID of the Raman spectrum of the conductive paste.
[0088] In some embodiments, the thixotropic index of the conductive paste may be 5 to 15. This allows the conductive paste to have a suitable viscosity, thereby allowing the conductive paste to have a high stability, which facilitates the practical application of the conductive paste.
[0089] In some embodiments, the viscosity of the conductive paste may be 2000 mPa·s to 8000 mPa·s. The viscosity here may also be understood as the rheological viscosity of the conductive paste, which can make the conductive paste have higher stability and facilitate the practical application of the conductive paste.
[0090] The present application also provides a method for preparing a conductive paste. Figure 1 This is a schematic diagram of a method for preparing a conductive paste provided in an embodiment of the present application. Please refer to Figure 1 , the preparation method of the conductive paste provided in the embodiment of the present application comprises:
[0091] Step S101: mixing single-walled carbon nanotubes, a first dispersant and a first solvent, and dispersing them uniformly to obtain a first mixture; in an X-ray diffraction analysis, the half-width of the diffraction peak of the single-walled carbon nanotubes in the 2θ range of 20° to 30° is 5° to 12°;
[0092] Step S102: mixing graphene, a second dispersant and a second solvent, and dispersing them uniformly to obtain a second mixture; the mass ratio of the single-walled carbon nanotubes to the graphene is 1:9 to 1:1;
[0093] Step S103: Mix the first mixture and the second mixture, and disperse them uniformly to obtain a conductive paste.
[0094] In the embodiment of the present application, the half-width of the diffraction peak of the single-walled carbon nanotube in the 2θ range of 20° to 30° is controlled to be 5° to 12°, for example, it can be 5°, 6°, 7°, 8°, 9°, 10°, 11°, 12° or any value between any two of the above numerical ranges, so that the single-walled carbon nanotube has a suitable degree of graphitization, thereby having high conductivity, high flexibility and high dispersibility, and the mass ratio of the single-walled carbon nanotube to the graphene is controlled to be 1:9 to 1:1, for example, it can be 1:1, 1:2, 1:3, 1:4, 1:5 , 1:6, 1:7, 1:8, 1:9 or any value between any two of the above numerical ranges, so that the prepared conductive slurry has better conductivity and suitable viscosity, when the conductive material is applied to the negative electrode material, the single-walled carbon nanotubes with high conductivity, high flexibility and high aspect ratio and the graphene with two-dimensional planar structure and high conductivity can be better connected to form a dense and complete conductive network, tightly coating the negative electrode material, thereby inhibiting the expansion of the negative electrode material, and then being able to effectively improve the cycle performance of the battery while ensuring the conductive performance.
[0095] It should be understood that, although the steps in the above flowchart are shown in sequence as indicated by the arrows, these steps are not necessarily performed in the order indicated by the arrows. Moreover, at least a portion of the steps in the above flowchart may include multiple steps or multiple stages, and these steps or stages are not necessarily performed at the same time or performed in sequence.
[0096] In the actual preparation process, the dispersion treatment in step S101 may include a homogenization treatment. Specifically, for example, a homogenizer may be used for high-pressure homogenization treatment, wherein the homogenization pressure may be, for example, 40Mpa to 60Mpa, and the number of homogenizations may be 1 to 5 times. Of course, the present application does not exclude the use of other processes, such as ball milling, sand milling, or ultrasonic dispersion, for dispersion treatment, as long as the particle size of the first mixture can be controlled within an appropriate range.
[0097] In some embodiments, the particle size D50 of the first mixture may be 5 μm to 50 μm. Controlling the particle size D50 of the first mixture within the above range can fully disperse the single-walled carbon nanotubes, facilitating the subsequent preparation of a high-quality conductive paste.
[0098] In some specific embodiments, in step S101, after the single-walled carbon nanotubes, the first dispersant and the first solvent are mixed, a pretreatment may be performed first, and then a dispersion treatment may be performed. The pretreatment may include, for example, a high-speed dispersion pretreatment, and the line speed of the pretreatment may be, for example, 30 m / s to 50 m / s. A premixed slurry with a relatively large particle size may be formed by the pretreatment, and the particle size D50 of the premixed slurry may be, for example, 50 μm to 200 μm, which can improve the effect and efficiency of the subsequent dispersion treatment.
[0099] Exemplarily, the first dispersant in step S101 may include one or more of polyvinyl pyrrolidone, polyvinyl alcohol, silane coupling agent, polyacrylic acid, carboxymethyl cellulose salt, ethyl cellulose, hydroxypropyl cellulose, chitosan, etc. The first solvent may include one or more of water, ethanol, isopropanol, etc. In a specific embodiment, the first dispersant is sodium carboxymethyl cellulose, and the first solvent is deionized water.
[0100] The IG / ID of the Raman spectrum of the single-walled carbon nanotubes in step S101 can be 40 to 120. In this way, the surface defect level of the single-walled carbon nanotubes can be moderate, taking into account good conductivity, flexibility and dispersibility. The single-walled carbon nanotubes can be better dispersed in the first solvent to form a uniform and dense conductive network, so that the conductive performance of the final conductive slurry is better. Due to the good flexibility of the single-walled carbon nanotubes, when the conductive slurry is applied to the negative electrode material, the conductive network formed by the single-walled carbon nanotubes and graphene can better suppress the volume expansion of the negative electrode material, thereby better improving the cycle performance of the battery.
[0101] The specific surface area of the single-walled carbon nanotubes in step S101 can be 500 m 2 / g~1200m 2 In this way, the single-walled carbon nanotubes are more dispersed, and the viscosity of the conductive paste finally prepared is suitable, and the conductive performance is better.
[0102] The purity of the single-walled carbon nanotubes in step S101 can be greater than or equal to 99%. In this way, there are almost no impurities in the single-walled carbon nanotubes, and they have better conductivity, thereby further improving the conductivity of the conductive paste finally obtained. Furthermore, the purity of the single-walled carbon nanotubes can be greater than 99%.
[0103] In the actual preparation process, the dispersion treatment in step S102 may include a homogenization treatment. Specifically, for example, a homogenizer may be used for high-pressure homogenization treatment, wherein the homogenization pressure may be, for example, 60 MPa to 100 MPa, and the number of homogenizations may be 5 to 20 times. Of course, the present application does not exclude the use of other processes, such as ball milling, sand milling, or ultrasonic dispersion, for dispersion treatment, as long as the particle size of the second mixture can be controlled within a suitable range.
[0104] In some embodiments, the particle size D50 of the second mixture is less than or equal to 6 μm. Controlling the particle size D50 of the second mixture within the above range can fully disperse the graphene, facilitating the subsequent preparation of a high-quality conductive paste. Further, the particle size D50 of the second mixture is less than 6 μm.
[0105] In some specific embodiments, in step S102, after the graphene, the second dispersant and the second solvent are mixed, a pretreatment may be performed first, and then a dispersion treatment may be performed. The pretreatment may include, for example, a high-speed dispersion pretreatment, and the line speed of the pretreatment may be, for example, 30 m / s to 50 m / s. The pretreatment may first form a premixed slurry with a relatively large particle size, and the particle size D50 of the premixed slurry may be, for example, 50 μm to 120 μm, which may improve the effect and efficiency of the subsequent dispersion treatment.
[0106] Exemplarily, the second dispersant in step S102 may include one or more of polyvinyl pyrrolidone, polyvinyl alcohol, silane coupling agent, polyacrylic acid, carboxymethyl cellulose salt, ethyl cellulose, hydroxypropyl cellulose, chitosan, etc. The second solvent may include one or more of water, ethanol, isopropanol, etc. In a specific embodiment, the second dispersant is sodium carboxymethyl cellulose, and the second solvent is deionized water.
[0107] The IG / ID of the Raman spectrum of the graphene in step S102 may be 1 to 10. In this way, the graphene can have both good conductivity and dispersibility, so that the finally prepared conductive paste has good conductivity and suitable viscosity.
[0108] The specific surface area of the graphene in step S102 can be 20 m 2 / g~100m 2 In this way, the dispersion of graphene is more favorable, and the viscosity of the finally prepared conductive paste can be made appropriate, and the conductive performance is better.
[0109] The purity of the graphene in step S102 can be greater than or equal to 99%. In this way, the graphene contains almost no impurities and has better conductivity, thereby further improving the conductivity of the conductive paste. Furthermore, the purity of the graphene can be greater than 99%.
[0110] In the actual preparation process, the dispersion treatment in step S103 may include, for example, mixing and stirring dispersion, the mixing and stirring dispersion line speed may be 5m / s to 15m / s, and the stirring time may be 20min to 60min. In this way, the first mixture and the second mixture can be mixed more fully, thereby further improving the quality of the conductive paste obtained.
[0111] The particle sizes D90 and D50 of the conductive paste prepared in step S103 satisfy: D90 / D50 is 2 to 8. In this way, the conductive paste can have better conductive properties and stability.
[0112] The IG / ID of the Raman spectrum of the conductive paste prepared in step S103 may be 10 to 60. This ensures that the conductive paste has good conductive properties.
[0113] The thixotropic index of the conductive paste prepared in step S103 may be 5 to 15. In this way, the conductive paste may have a suitable viscosity, thereby making the conductive paste have a high stability, which is convenient for practical application of the conductive paste.
[0114] The viscosity of the conductive paste prepared in step S103 may be 2000 mPa·s to 8000 mPa·s, so that the conductive paste has a higher stability, which is convenient for practical application of the conductive paste.
[0115] The length of the single-walled carbon nanotubes in the conductive paste prepared in step S103 can be 1 μm to 30 μm. In this way, the viscosity of the conductive paste can be appropriate and the conductive performance can be good. When the conductive paste is applied to the negative electrode material, the single-walled carbon nanotubes and graphene are interconnected to form a dense and stable conductive network, which can better coat the negative electrode material, thereby better suppressing the volume expansion of the negative electrode material, and further improving the cycle performance of the battery.
[0116] The diameter of the bundle of single-walled carbon nanotubes in the conductive slurry prepared in step S103 can be 10nm to 50nm. This can form a better and more stable connection between the single-walled carbon nanotubes and graphene, facilitating the formation of a denser and more stable conductive network. In the actual application of negative electrode materials, the volume expansion of negative electrode materials can be better suppressed, thereby further improving the cycle performance of the battery.
[0117] The number of graphene layers in the conductive paste prepared in step S103 may be less than or equal to 10. This can make the graphene sheets in the conductive paste smaller in diameter and more dispersible, more conducive to interconnection with the single-walled carbon nanotubes, and the coating effect of the conductive network formed by the single-walled carbon nanotubes and graphene is better. Further, the number of graphene layers may be less than 10.
[0118] Taking the total weight of the conductive paste as 100%, in the conductive paste prepared in step S103, the weight percentage of the single-walled carbon nanotubes can be 0.05% to 0.5%, the weight percentage of the graphene can be 0.25% to 2.5%, the sum of the weight percentages of the first dispersant and the second dispersant can be 0.2% to 1%, and the sum of the weight percentages of the first solvent and the second solvent can be 96% to 99.5%. In this way, the single-walled carbon nanotubes and graphene can be more evenly dispersed in the solvent, forming a conductive paste with good conductivity, appropriate viscosity and high stability, thereby facilitating the application of the conductive paste.
[0119] The embodiments of the present application also provide a use of the conductive paste described in any of the above embodiments or the conductive paste prepared by the preparation method of the conductive paste described in any of the above embodiments in a lithium-ion battery.
[0120] The conductive paste described in any of the above embodiments or the conductive paste prepared by the preparation method described in any of the above embodiments has excellent conductivity and suitable viscosity, and can be used in positive electrode materials and negative electrode materials of lithium-ion batteries, and is particularly suitable for use in negative electrode materials. This is because, in the conductive paste, single-walled carbon nanotubes with high conductivity, high flexibility and high aspect ratio and graphene with two-dimensional planar structure and high conductivity can be well connected to form a dense and complete conductive network, tightly coating the negative electrode material, thereby inhibiting the expansion of the negative electrode material, and thus effectively improving the battery's cycle performance while ensuring the conductive performance.
[0121] The technical solution of the present application is further described below in combination with a plurality of embodiments and comparative examples.
[0122] Example 1
[0123] Step S101: After the single-walled carbon nanotubes, sodium carboxymethyl cellulose and deionized water are mixed and dispersed at high speed for 15 minutes, the mixture is homogenized three times at a pressure of 50 MPa using a homogenizer to obtain a mixture I (a first mixture); wherein the XRD diffraction angle 2θ of the single-walled carbon nanotubes is 25.48°, the XRD half-height width is 8.21°, and the specific surface area is 810.21 m 2 / g, IG / ID is 62.23;
[0124] Step S102: After the graphene, sodium carboxymethyl cellulose and deionized water are mixed and dispersed at high speed for 30 minutes, a homogenizer is used to homogenize 10 times at a pressure of 80 MPa to obtain a mixture II (a second mixture); wherein the XRD half-height width of the graphene is 0.51°, and the specific surface area is 30.23 m 2 / g.
[0125] Step S103: Mixing and dispersing mixture I and mixture II at a linear speed of 7 m / s for 30 min to obtain a conductive paste. Based on 100 parts by total weight of the conductive paste, the conductive paste includes 0.3 parts of single-walled carbon nanotubes, 0.7 parts of graphene, 0.4 parts of sodium carboxymethyl cellulose and 98.6 parts of deionized water.
[0126] Example 2
[0127] The preparation method of the conductive paste in this embodiment is basically the same as that in Embodiment 1, except that:
[0128] Based on 100 parts of the total weight of the conductive paste, the conductive paste obtained in step S103 includes 0.1 parts of single-walled carbon nanotubes, 0.9 parts of graphene, 0.4 parts of sodium carboxymethyl cellulose and 98.6 parts of deionized water.
[0129] Example 3
[0130] The preparation method of the conductive paste in this embodiment is basically the same as that in Embodiment 1, except that:
[0131] Based on 100 parts of the total weight of the conductive paste, the conductive paste obtained in step S103 includes 0.5 parts of single-walled carbon nanotubes, 0.5 parts of graphene, 0.4 parts of sodium carboxymethyl cellulose and 98.6 parts of deionized water.
[0132] Example 4
[0133] The preparation method of the conductive paste in this embodiment is basically the same as that in Embodiment 1, except that:
[0134] The XRD diffraction angle 2θ of the single-walled carbon nanotube in step S101 is 26.41°, the XRD half-height width is 6.52°, and the specific surface area is 822.25 m 2 / g, IG / ID is 90.45.
[0135] Example 5
[0136] The preparation method of the conductive paste in this embodiment is basically the same as that in Embodiment 1, except that:
[0137] The XRD diffraction angle 2θ of the single-walled carbon nanotubes in step S101 is 23.19°, the XRD half-height width is 11.74°, and the specific surface area is 815.32 m 2 / g, IG / ID is 50.82.
[0138] Comparative Example 1
[0139] The preparation method of the conductive paste in this comparative example is basically the same as that in Example 1, except that:
[0140] Based on 100 parts of the total weight of the conductive paste, the conductive paste obtained in step S103 includes 0.8 parts of single-walled carbon nanotubes, 0.2 parts of graphene, 0.4 parts of sodium carboxymethyl cellulose and 98.6 parts of deionized water.
[0141] Comparative Example 2
[0142] The preparation method of the conductive paste in this comparative example is basically the same as that in Example 1, except that:
[0143] Based on 100 parts of the total weight of the conductive paste, the conductive paste obtained in step S103 includes 0.1 parts of single-walled carbon nanotubes, 1.5 parts of graphene, 0.4 parts of sodium carboxymethyl cellulose and 98 parts of deionized water.
[0144] Comparative Example 3
[0145] The preparation method of the conductive paste in this comparative example is basically the same as that in Example 1, except that:
[0146] The XRD diffraction angle 2θ of the single-walled carbon nanotube in step S101 is 25.45°, the XRD half-height width is 16.24°, and the specific surface area is 820.21 m 2 / g, IG / ID is 40.18.
[0147] Comparative Example 4
[0148] The preparation method of the conductive paste in this comparative example is basically the same as that in Example 1, except that:
[0149] The XRD diffraction angle 2θ of the single-walled carbon nanotube in step S101 is 25.76°, the XRD half-height width is 4.78°, and the specific surface area is 805.34 m 2 / g, IG / ID is 122.34.
[0150] In order to verify the performance of the conductive pastes prepared in the above embodiments and comparative examples, the performance of the conductive pastes obtained in the above embodiments and comparative examples was tested. The specific tests are as follows:
[0151] (I) Physical properties test of conductive paste
[0152] The D90 / D50, thixotropic index and IG / ID of the Raman spectrum of the conductive pastes obtained in Examples 1 to 5 and Comparative Examples 1 to 4 were tested, and the specific tests are as follows:
[0153] (1) D90 / D50 test of conductive paste: After diluting the conductive paste 10 times, add it to the Malvern laser particle size analyzer for testing. The average value of D50 obtained from three tests is taken as the D50 of the conductive paste, and the average value of D90 obtained from three tests is taken as the D90 of the conductive paste. Based on the D50 and D90 of the conductive paste, the D90 / D50 of the conductive paste is calculated.
[0154] (2) Thixotropic index test of conductive paste: A rotational rheometer was used to test the viscosity at a variable shear rate from 0 r / s to 100 r / s. The ratio of the viscosity at the 5.6 r / s to the 65 r / s was the thixotropic index.
[0155] (3) IG / ID test of Raman spectrum of conductive paste: The conductive paste is coated on polyethylene terephthalate (PET), dried and then subjected to Raman spectrum test to obtain IG / ID of Raman spectrum of the conductive paste.
[0156] The test results are shown in Table 1.
[0157] (II) Conductive performance test of conductive paste: The main material of the negative electrode material is silicon dioxide (SiO x , wherein 0<x≤2), conductive paste and polyacrylic acid binder (PAA) were fully mixed in a mass ratio of 98.5:0.5:1 to obtain a mixed slurry (the sum of the mass proportions of single-walled carbon nanotubes and graphene in the mixed slurry was 0.3%), and the mixed slurry was coated on the surface of the PET film with a coating thickness of 200μm. After drying at 80℃ for 10min, the volume resistivity was tested using a four-probe resistance tester. The test results of the volume resistivity are shown in Table 1.
[0158] (III) Battery cycle performance test: After silicon dioxide, conductive slurry and PAA are fully mixed at a mass ratio of 98.5:0.5:1, a mixed slurry is obtained (the sum of the mass proportions of single-walled carbon nanotubes and graphene in the mixed slurry is 0.3%), and the mixed slurry is coated on the surface of the current collector with a wet material thickness of 200μm. After drying at 80°C for 10 minutes, it is used as a negative electrode sheet; a lithium sheet is used as the positive electrode to prepare a CR2032 button battery, which is tested in the Blue Electric test system. The charge and discharge conditions are set as follows: first, the button battery is discharged at a constant current of 0.1C rate to a voltage of 0.005V; then, it is charged at a constant current of 0.1C rate to a voltage of 3V, and the initial capacity of the battery is recorded as Q 初始 , cycle test 500 times, record the battery capacity after 500 cycles as Q 500圈 , battery 500 cycle capacity retention rate = (Q 500圈 / Q 初始)×100%. The test results of the capacity retention rate of the battery after 500 cycles are shown in Table 1.
[0159] Table 1
[0160]
[0161]
[0162] According to the data of Examples 1 to 3 and Comparative Examples 1 and 2 in Table 1, it can be seen that as the mass ratio of single-walled carbon nanotubes to graphene increases, the D90 / D50 of the conductive paste gradually increases. When the mass ratio of single-walled carbon nanotubes to graphene is greater than 1:1, the conductive paste is difficult to disperse and the dispersion effect is poor. Therefore, relative to Examples 1 to 3, the thixotropic index of the conductive paste in Comparative Example 1 is larger, that is, the viscosity of the conductive paste is higher, and the IG / ID of the Raman spectrum of the conductive paste is higher, which leads to a lower volume resistivity of the conductive paste and a lower capacity retention rate of the battery after 500 cycles. This is because the content of single-walled carbon nanotubes in the conductive paste is relatively high, and the content of graphene is relatively low, and a dense conductive network cannot be formed. Therefore, the conductive performance is poor. Since the single-walled carbon nanotubes and graphene cannot form a conductive network that effectively covers the negative electrode material to inhibit the volume expansion of the negative electrode material, during the battery cycle, the single-walled carbon nanotubes are prone to rupture due to the expansion of the negative electrode material, which reduces the battery cycle life. When the mass ratio of single-walled carbon nanotubes to graphene is less than 1:9, the content of graphene in the conductive paste is higher and the content of single-walled carbon nanotubes is lower, and it is difficult for single-walled carbon nanotubes to play an effective bridging role, that is, single-walled carbon nanotubes cannot effectively connect with graphene to form a dense conductive network. Therefore, relative to Examples 1 to 3, the volume resistivity of the conductive paste in Comparative Example 2 is higher, and accordingly, the capacity retention rate of the battery after 500 cycles is lower.
[0163] According to the data of Example 1, Comparative Example 3 and Comparative Example 4 in Table 1, it can be seen that when the XRD half-height width of the single-walled carbon nanotube is less than 5°, due to the high degree of graphitization of the single-walled carbon nanotube, the single-walled carbon nanotube has high conductivity and flexibility, but the dispersibility of the single-walled carbon nanotube is poor, and it is not easy to disperse evenly in the conductive paste, so that the thixotropic index of the conductive paste is high, which is not conducive to forming a uniform and dense conductive network. Therefore, relative to Example 1, the volume resistivity of the conductive paste in Comparative Example 4 is higher, and accordingly, the capacity retention rate of the battery after 500 cycles is low. When the XRD half-height width of the single-walled carbon nanotube is greater than 12°, due to the low degree of graphitization of the single-walled carbon nanotube, the conductivity and flexibility of the single-walled carbon nanotube are poor, which also affects the conductivity of the conductive paste. Therefore, relative to Example 1, the volume resistivity of the conductive paste in Comparative Example 3 is higher, and accordingly, the capacity retention rate of the battery after 500 cycles is lower.
[0164] Combined with the data in Table 1, the volume resistivity of the conductive pastes in Examples 1 to 5 is significantly lower than that of the conductive pastes in Comparative Examples 1 to 4, which indicates that by controlling the half-width (XRD half-width) of the diffraction peak of the single-walled carbon nanotube in the 2θ range of 20° to 30° to 5° to 12°, the single-walled carbon nanotube can have a suitable degree of graphitization, thereby having high conductivity, high flexibility and high dispersibility, and by controlling the mass ratio of the single-walled carbon nanotube to graphene to 1:9 to 1:1, the conductive paste can have better conductivity and suitable viscosity (i.e., having a suitable thixotropic index). It can also be seen from the data in Table 1 that the capacity retention rate of the battery containing the conductive pastes in Examples 1 to 5 in the negative electrode material after 500 cycles is significantly higher than the capacity retention rate of the battery containing the conductive pastes in Comparative Examples 1 to 4 in the negative electrode material after 500 cycles. This shows that in the embodiments of the present application, when the conductive material is applied to the negative electrode material, the single-walled carbon nanotubes with high conductivity, high flexibility and high aspect ratio and the graphene with two-dimensional planar structure and high conductivity can be well connected to form a dense and complete conductive network, tightly coating the negative electrode material, thereby inhibiting the expansion of the negative electrode material, and thus effectively improving the cycle performance of the battery while ensuring the conductive performance.
[0165] Figures 2 to 4 The following are scanning electron microscope images of the conductive pastes in Examples 1 to 3 respectively. Figure 2 It can be seen that the sheet diameter of graphene in the conductive paste of Example 1 (eg Figure 2 The length of the single-walled carbon nanotube is about 20 μm. Figure 3 It can be seen that the sheet diameter of graphene in the conductive paste of Example 2 (eg Figure 3 The length of the single-walled carbon nanotube is about 15 μm. Figure 4 It can be seen that the sheet diameter of graphene in the conductive paste of Example 3 (eg Figure 4 The length of the single-walled carbon nanotube is about 18 μm. Figure 5 is a transmission electron microscope image of the conductive paste in Example 1, Figure 5 It can be seen that the number of graphene layers in the conductive paste is less than 10.
[0166] Figure 6 and Figure 7 The following are scanning electron microscope images of the conductive pastes in Comparative Example 1 and Comparative Example 2, respectively. Figure 6 It can be seen that since the mass ratio of single-walled carbon nanotubes to graphene in the conductive paste in Comparative Example 1 is too large, the conductive paste is basically single-walled carbon nanotubes, and the content of graphene is very small. Figure 6 and Figures 2 to 4 It can be seen from the comparison that the high content of single-walled carbon nanotubes in the conductive paste makes it easy for the single-walled carbon nanotubes to be entangled, resulting in poor dispersion and high viscosity of the conductive paste. Figure 7 It can be seen that since the mass ratio of single-walled carbon nanotubes to graphene in the conductive paste in Comparative Example 2 is too small, the conductive paste is basically graphene, and the content of single-walled carbon nanotubes is very small. Figure 7 and Figures 2 to 4 It can be seen from the comparison that graphene with a two-dimensional structure is difficult to bridge well to form a perfect conductive network. Therefore, the volume resistivity of the conductive pastes in Comparative Examples 1 and 2 is relatively high, and accordingly, the capacity retention rate of the battery after 500 cycles is relatively low.
[0167] Figure 8 is a scanning electron microscope image of the negative electrode material containing the conductive paste in Example 1, Figure 8 It can be seen that both graphene and single-walled carbon nanotubes cover the surface of silicon oxide, the main material of the negative electrode material, well (such as Figure 8 The negative electrode material has a good conductive network, and thus has a good coating effect, which is beneficial to improving the conductivity of the negative electrode material and can better inhibit the expansion of the negative electrode material, thereby improving the cycle performance of the battery, which is consistent with the test results in Table 1.
[0168] Fig. 9 and Fig.10 The following are scanning electron microscope images of the negative electrode materials containing the conductive pastes in Comparative Example 1 and Comparative Example 2, respectively. Fig. 9 It can be seen that since the mass ratio of single-walled carbon nanotubes to graphene in the conductive paste in Comparative Example 1 is too large, the conductive paste is basically composed of single-walled carbon nanotubes and the content of graphene is very small. Therefore, the surface of the main material of the negative electrode material, silicon oxide, is basically covered with single-walled carbon nanotubes (such as Fig. 9 The graphene content is very low and lacks a certain degree of coating, so it cannot form a good conductive network to coat the negative electrode material to inhibit the expansion of the negative electrode material. During the battery cycle, the volume of the negative electrode material changes greatly, which can easily lead to the breakage of the single-walled carbon nanotubes, thereby affecting the battery's cycle performance. Fig.10 It can be seen that since the mass ratio of single-walled carbon nanotubes to graphene in the conductive paste in Comparative Example 2 is too small, the conductive paste is basically graphene, and the content of single-walled carbon nanotubes is very small. Therefore, the negative electrode material is mainly graphene (such as Fig.10The single-walled carbon nanotubes (shown in the solid line frame) have little content and lack of wrapping properties. It is difficult for individual graphene to bridge each other to form a complete conductive network to coat the negative electrode material to inhibit the expansion of the negative electrode material, thereby affecting the cycle performance of the battery. Therefore, the battery capacity retention rate of Comparative Example 1 and Comparative Example 2 after 500 cycles is low.
[0169] In the present application, single-walled carbon nanotubes and graphene are compounded to obtain a conductive slurry. Single-walled carbon nanotubes with excellent performance are selected by the XRD half-width of the single-walled carbon nanotubes. By controlling the mass ratio of the single-walled carbon nanotubes to the graphene, the particle size, IG / ID of the Raman spectrum and the thixotropy of the conductive slurry are all within a suitable range. In this way, when the conductive slurry is used in the negative electrode material of the battery, it can maintain excellent conductivity. At the same time, due to the two-dimensional structural characteristics of the graphene, it can coat the single-walled carbon nanotubes and the silicon-based negative electrode material. The single-walled carbon nanotubes provide a three-dimensional conductive network, and the graphene provides a two-dimensional conductive network. Under the synergistic effect of the single-walled carbon nanotubes and the graphene, a uniform, dense and perfect conductive network can be formed on the surface of the silicon-based negative electrode material. The silicon-based negative electrode material is in close contact with the conductive network. On the one hand, the conductive performance of the negative electrode material can be guaranteed, and on the other hand, the expansion of the silicon-based negative electrode material can be suppressed, and the single-walled carbon nanotubes will not be easily broken when the silicon-based negative electrode material expands, so the cycle life of the battery can be effectively increased.
[0170] It should be noted that the conductive paste embodiments, conductive paste preparation method embodiments and conductive paste application embodiments in lithium-ion batteries provided in the present application belong to the same concept; the technical features in the technical solutions recorded in the embodiments can be arbitrarily combined without conflict.
[0171] It should be understood that the above embodiments are exemplary and are not intended to include all possible implementations. Various modifications and changes may be made on the basis of the above embodiments without departing from the scope of the present disclosure. Similarly, the various technical features of the above embodiments may be arbitrarily combined to form other embodiments of the present invention that may not be explicitly described. Therefore, the above embodiments only express several implementations of the present invention and do not limit the scope of protection of the patent of the present invention.
Claims
1. A conductive paste, characterized in that: including single-walled carbon nanotubes and graphene; The mass ratio of the single-walled carbon nanotube to the graphene is 1:9 to 1:1; In X-ray diffraction analysis, the half-width of the diffraction peak of the single-walled carbon nanotube in the 2θ range of 20° to 30° is 5° to 12°.
2. The conductive paste according to claim 1, characterized in that: The conductive paste also includes a dispersant and a solvent. Taking the total weight of the conductive paste as 100%, the weight percentage of the single-walled carbon nanotubes is 0.05% to 0.5%, the weight percentage of the graphene is 0.25% to 2.5%, the weight percentage of the dispersant is 0.2% to 1%, and the weight percentage of the solvent is 96% to 99.5%.
3. The conductive paste according to claim 1, characterized in that: The single-walled carbon nanotubes satisfy at least one of the following characteristics: (1) The IG / ID of the Raman spectrum of the single-walled carbon nanotube is 40 to 120; preferably, the IG / ID of the Raman spectrum of the single-walled carbon nanotube is 50 to 90; (2) The specific surface area of the single-walled carbon nanotube is 500 m 2 / g~1200m 2 / g; (3) The purity of the single-walled carbon nanotubes is greater than or equal to 99%; (4) The length of the single-walled carbon nanotube is 1 μm to 30 μm; (5) The diameter of the bundle of single-walled carbon nanotubes is 10 nm to 50 nm.
4. The conductive paste according to claim 1, characterized in that: The graphene satisfies at least one of the following characteristics: (1) IG / ID of the Raman spectrum of the graphene is 1 to 10; (2) The specific surface area of the graphene is 20 m 2 / g~100m 2 / g; (3) The purity of the graphene is greater than or equal to 99%; (4) The number of graphene layers is less than or equal to 10.
5. The conductive paste according to any one of claims 1 to 4, characterized in that: The conductive paste satisfies at least one of the following characteristics: (1) The particle sizes D90 and D50 of the conductive paste satisfy: D90 / D50 is 2 to 8; (2) the IG / ID of the Raman spectrum of the conductive paste is 10 to 60; (3) The thixotropic index of the conductive paste is 5 to 15; (4) The viscosity of the conductive paste is 2000 mPa·s to 8000 mPa·s.
6. A method for preparing a conductive paste, characterized in that: The method comprises: The single-walled carbon nanotubes, the first dispersant and the first solvent are mixed and dispersed uniformly to obtain a first mixture; in an X-ray diffraction analysis, the half-height width of the diffraction peak of the single-walled carbon nanotubes in the 2θ range of 20° to 30° is 5° to 12°; The graphene, the second dispersant and the second solvent are mixed and dispersed uniformly to obtain a second mixture; the mass ratio of the single-walled carbon nanotube to the graphene is 1:9 to 1:1; The first mixture and the second mixture are mixed and dispersed uniformly to obtain the conductive paste.
7. The method for preparing the conductive paste according to claim 6, characterized in that: The step of preparing the first mixture satisfies at least one of the following characteristics: (1) The IG / ID of the Raman spectrum of the single-walled carbon nanotube is 40 to 120; (2) The specific surface area of the single-walled carbon nanotube is 500 m 2 / g~1200m 2 / g; (3) The purity of the single-walled carbon nanotubes is greater than or equal to 99%; (4) The particle size D50 of the first mixture is 5 μm to 50 μm.
8. The method for preparing the conductive paste according to claim 6, characterized in that: The step of preparing the second mixture satisfies at least one of the following characteristics: (1) IG / ID of the Raman spectrum of the graphene is 1 to 10; (2) The specific surface area of the graphene is 20 m 2 / g~100m 2 / g; (3) The purity of the graphene is greater than or equal to 99%; (4) The particle size D50 of the second mixture is less than or equal to 6 μm.
9. The method for preparing the conductive paste according to any one of claims 6 to 8, characterized in that: The conductive paste satisfies at least one of the following characteristics: (1) The particle sizes D90 and D50 of the conductive paste satisfy: D90 / D50 is 2 to 8; (2) the IG / ID of the Raman spectrum of the conductive paste is 10 to 60; (3) The thixotropic index of the conductive paste is 5 to 15; (4) The viscosity of the conductive paste is 2000 mPa·s to 8000 mPa·s; (5) The length of the single-walled carbon nanotubes in the conductive paste is 1 μm to 30 μm; (6) The diameter of the bundle of single-walled carbon nanotubes in the conductive paste is 10 nm to 50 nm; (7) The number of graphene layers in the conductive paste is less than or equal to 10; (8) Taking the total weight of the conductive paste as 100%, in the conductive paste, the weight percentage of the single-walled carbon nanotubes is 0.05% to 0.5%, the weight percentage of the graphene is 0.25% to 2.5%, the sum of the weight percentages of the first dispersant and the second dispersant is 0.2% to 1%, and the sum of the weight percentages of the first solvent and the second solvent is 96% to 99.5%.
10. Use of the conductive paste according to any one of claims 1 to 5 or the conductive paste prepared by the method for preparing the conductive paste according to any one of claims 6 to 9 in lithium-ion batteries.